Profesionalisme Penyuluh Dalam Implementasi Program Kampung Keluarga Berkualitas (Kb) di Kota Pekanbaru - Azra Alfia Fitri; Adianto Adianto (Peneliti.net, 2022)
Pekanbaru City is one of the cities with a population of 1,028,237 people. This will have an impact on uncontrolled population growth if it is not immediately overcome by implementing the maximum family planning program. The role of extension workers is very important in providing information regarding the importance of implementing family planning. So to be able to assess the implementation of family planning counseling, it is necessary to assess based on skills, professionalism, and responsibility and identify inhibiting factors in the implementation of the kb program counseling. In carrying out this research, researchers used qualitative methods with a descriptive approach. The results of this study also explained that the implementation of counseling for the family planning program by extension workers during the Covid-19 pandemic has been maximized. information because the use of this technology is one of the connecting media in providing information, the number of Human Resources (HR), namely extension workers, needs to be increased in quantity and there is still low community participation in carrying out the family planning (KB) program.